Using Shulman's Pedagogical Reasoning Model to improve strength and conditioning coaching - Holt, A. (Journal of Australian Strength and Conditioning, 2016)
There is considerable focus in the strength and conditioning literature on enhancing professional development through discussion of optimal selection and application of exercises. However effective strength and conditioning coaching requires the development of a range of additional skills such as communication skills, problem solving skills, reflection skills and the ability to transform knowledge into a form that can be readily understood by athletes. There is limited literature in the field to guide strength and conditioning coaches in the development of these skills. In this paper it is argued that coaching shares many similarities with teaching and consequently strength and conditioning coaches may benefit from the application of models of expertise development in teaching. This paper explores the similarities between coaching and teaching and how the application of Shulman`s pedagogical reasoning model in everyday coaching environments may assist strength and conditioning coaches to develop their professional expertise and improve their effectiveness as coaches.